Differences in Student Career Adaptability: Education Level and Gender - Harum, Akhmad; Hikmah, Muh Syawal (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
The research aims to provide a deeper understanding of differences in student career adaptability based on educational level and gender. The research results provide a valuable contribution to developing programs to improve Student Career Adaptability. This research uses quantitative description. The subjects of the study were 981 students in South Sulawesi who were spread out at the junior high school, high school, and vocational school levels and by gender. The research instrument uses a scale adaptation from the Indonesian version of Savickas & Porfeli (Panjaitan and Sahrah, 2023)Career Adapt-Abilities Scale–Short Form (CAAS-SF) which is valid and reliable using the confirmatory factor analysis test with JASP—data analysis using ANOVA. The results showed that the students' Career Adaptability in the study had a high level, and there was no significant difference based on education level except for the control/control aspect, and there was no significant difference based on gender except for the attention/caring part. These results provide insight into students' Career Adaptability in the context of educational level and gender